2023
DOI: 10.1109/access.2023.3236814
|View full text |Cite
|
Sign up to set email alerts
|

A Contextual Multimodal System for Increasing Situation Awareness and Takeover Quality in Conditionally Automated Driving

Abstract: This work involved human subjects or animals in its research. Approval of all ethical and experimental procedures and protocols was granted by the Ethics Committee of the University of Fribourg under Approval No. 445.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…Kim et al reported that the complexity of the road plays an additional role in the recovery of situational awareness and should be taken into account [40]. Capallera et al constructed a multimodal system to increase situational awareness by conveying information about the driving environment [41]. Their system was able to increase drivers' situational awareness but did not show positive effects on TO quality.…”
Section: Non-driving Related Tasks and Situational Awarenessmentioning
confidence: 99%
“…Kim et al reported that the complexity of the road plays an additional role in the recovery of situational awareness and should be taken into account [40]. Capallera et al constructed a multimodal system to increase situational awareness by conveying information about the driving environment [41]. Their system was able to increase drivers' situational awareness but did not show positive effects on TO quality.…”
Section: Non-driving Related Tasks and Situational Awarenessmentioning
confidence: 99%